Effect of circadian rhythm and menstrual cycle on physical performance in women: a systematic review - Benícková, M.; Gimunová, M.; Paludo, A. C. (Frontiers in Physiology, 2024)
The literature has extensively investigated potential factors influencing women`s performance, including the menstrual cycle and the circadian rhythm. However, review articles exploring the combined influence of both factors remain lacking in the literature. The study aimed to systematically review the literature on the relationship between the circadian rhythm and menstrual cycle on physical performance in women. The review followed the PRISMA guidelines. The search was performed on the Web of Science, PubMed, Scopus, SPORTDiscus, and Google Scholar databases. Of the 1205 records identified, four articles met the inclusion criteria. From four articles, two studies found a significant interaction between the time of day and phase of the menstrual cycle with physical performance. The isometric strength increased in the afternoon in the mid-luteal phase (versus the morning in the mid-luteal phase, p < 0.05), and the maximum cycling power was higher in the afternoon in the mid-follicular phase (versus the morning in the mid-follicular phase, p < 0.01). Our findings suggest that the time of day and the menstrual cycle phase affect physical performance, with the daytime potentially having a more significant influence. However, the results should be interpreted cautiously due to the limited studies and diverse methodologies used to monitor the menstrual cycle phase. This review reinforces the need for further investigation to understand better the combined effects of the circadian rhythm and menstrual cycle on women`s physical performance.